Reconstruction of the differentiated long-term exhumation history of Fuerteventura, Canary Islands, Spain, through fission-track and (U-Th-Sm)/He data - Wipf, Martin; Glasmacher, Ulrich A.; Stockli, Daniel Fritz; Emmerich, Axel; Bechstädt, Thilo; Baur, Heinrich (International journal of earth sciences, 2010)
Miocene Intrusives and Lower Cretaceous siliciclastic sedimentary rocks from the Basal Complex in western-Fuerteventura were analyzed with low-temperature thermochronometric methods such as fission-track, and (U-Th-Sm)/He dating, in order to reveal the evolution of the island’s exhumation history. The obtained thermochronometric data yields a very slow rate of cooling in the order of 1.5-3°C/Myr from ~50 to 20 Ma for the Early Cretaceous siliciclastic rocks. These sedimentary units have never been heated significantly above 240°C after deposition and still record the submarine onset of the island’s formation in the Eocene. Intrusive bodies associated with the early Miocene magmatic activity of the central volcanic complex of the island show rapid initial cooling rates of 50-70°C/Myr from ~20 to 14 Ma. Contemporaneous with the intrusions the cooling rate of the Cretaceous sedimentary units increased to 25-35°C/Myr and it is inferred that this increase is associated with enhanced uplift and erosion of the Central Volcanic Complex. After ~14 Ma rates slowed down to 3-6°C/Myr. Palaeosols overlying the sedimentary units are themselves covered by Pliocene basalt flows and reveal that the sedimentary rocks reached the surface before ~5 Ma. The thermochronometric data obtained in this study for central Fuerteventura is difficult to reconcile with the cooling history derived from previously obtained fission-track and K-Ar data from the north-western part of the island. This inconsistency is likely to indicate that the exhumation history of Fuerteventura is more complex and regionally subdivided than previously believed.
Published: 24 January 2009
Gesehen am 15.03.2024